1986
DOI: 10.1021/bi00372a024
|View full text |Cite
|
Sign up to set email alerts
|

Subunits of luteinizing hormone-human chorionic gonodotropin receptor from bovine corpora lutea

Abstract: A batch of 24 mg of luteinizing hormone-human chorionic gonadotropin (LH-hCG) receptor was isolated from bovine corpora lutea. The LH-hCG receptor showed specific binding with hCG. The receptor-hCG complex activated the regulatory Ns protein isolated from rabbit liver, which in turn stimulated adenylate cyclase to convert ATP into cAMP in vitro, attesting to the biological activity of the purified LH-hCG receptor. The LH-hCG receptor was treated with 2% sodium dodecyl sulfate (SDS) to prepare the molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Even though luteal cell populations were altered by PGF and age of animal, existence of spare (unoccupied) receptors may have masked any influence of PGF or age on total LH receptors. Unoccupied receptor concentration ranged from .75 to 2.0 fmol/mg wet weight, which was similar to results (bovine) reported by Rutter et al (1985) and Spicer et al (1981), but was lower than results (bovine) reported by Saxena et al (1984). The lower receptor concentration observed in this study could be due to the animal model utilized: Bos indicus cattle have smaller CL that are less steroidogenically functional than Bos taurus cattle (Irvin et al, 1978;Segerson et al, 1984).…”
Section: Cell Type Iandllsupporting
confidence: 84%
“…Even though luteal cell populations were altered by PGF and age of animal, existence of spare (unoccupied) receptors may have masked any influence of PGF or age on total LH receptors. Unoccupied receptor concentration ranged from .75 to 2.0 fmol/mg wet weight, which was similar to results (bovine) reported by Rutter et al (1985) and Spicer et al (1981), but was lower than results (bovine) reported by Saxena et al (1984). The lower receptor concentration observed in this study could be due to the animal model utilized: Bos indicus cattle have smaller CL that are less steroidogenically functional than Bos taurus cattle (Irvin et al, 1978;Segerson et al, 1984).…”
Section: Cell Type Iandllsupporting
confidence: 84%
“…For example, whereas Kusuda and Dufau (10) identified the purified LH/hCG receptor as a single protein of Mr 73,000, Bruch et al (11) reported that the purified receptor consists of four nonidentical subunits of Mr 79,300, 64,400, 55,300, and 46,700, although in a subsequent study it was concluded that the receptor may exist as a single polypeptide (14). Saxena et al (12) reported that a Mr 120,000 protein represents the functional unit of the hCG receptor and that this Mr 120,000 protein is composed of Mr 85,000 and 38,000 proteins linked covalently through disulfide linkages. More recently, Rebois et al (8), on the basis of hydrodynamic properties, reported that the receptor is composed of two dissimilar subunits held together noncovalently: a hormonebinding subunit of Mr 76,000 and a Mr 50,000 component.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have appeared regarding the structure of the ovarian LH/CG receptor as determined by chemical crosslinking (2-4), by photoaffinity labeling (5-7), and by flotation in sucrose density gradients combined with gel filtration chromatography (8). Recently, more information about the ovarian LH/CG receptor has resulted from attempts by several laboratories to purify the receptor by affinity chromatography (9)(10)(11)(12)(13)(14)(15). The conclusions of these studies suggested that the receptor could be either a heteropolymer or a single polypeptide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Human chorionic gonadotropin, derived from the chorion, is LH-like and preferentially binds to the α subunit of the LH receptor (Hong et al, 1999). When the receptor complex, located on the small luteal cells (Mamluk et al, 1998), is bound by either hCG or LH, it acts through the adenylate cyclase pathway, catalyzing the conversion of ATP to cAMP (Saxena et al, 1986). Some actions of hCG include a luteotropic effect similar to LH (Donaldson and Hansel, 1965) and stimulation of synthesis of progesterone by the CL in vitro (Veenhuizen et al, 1972) and in vivo (Breuel et al, 1989).…”
Section: Induced Corpora Luteamentioning
confidence: 99%